Timing of the Final Nocturnal Meal and Hypoglycemia Risk in Fasting Individuals with Type 1 Diabetes: A Randomized Crossover Trial - Alamoudi, Reem; Alassiri, Mishary; Aljawhrji, Abdulrhman; Almaghrabi, Mazin; Basulayman, Dalia; Ramadan, Majed (Journal of Diabetes and Endocrine Practice, 2025)
Despite known risks, many individuals with type 1 diabetes (T1D) fast during Ramadan. Local studies have shown that breaking the fast due to hypoglycemia is common during the morning hours; however, the optimal timing of Suhoor (the predawn meal) has not been thoroughly investigated. Current guidelines recommend late Suhoor; however, this does not provide sufficient time for correction in case of insulin overdosing and can lead to breaking the fast in the early hours.To compare the risk of hypoglycemia in individuals with T1D fasting during Ramadan between an early Suhoor (90–120 minutes before dawn plus a predawn snack) and a late Suhoor (30 minutes before dawn).In this randomized crossover trial, participants with T1D were assigned to either an early or late Suhoor regimen for 1 week, then switched to the other regimen for the second week. Data were collected via questionnaires and flash continuous glucose monitoring (FCGM).Forty-four patients were enrolled (73.5% female, mean age 25 ± 5.9 years). During early versus late Suhoor, the proportion of individuals who broke their fast due to hypoglycemia was 64.5% versus 58.1% (p = 0.18). Most hypoglycemia episodes occurred during early fasting hours. Mean fast-breaking days were similar (2.5 vs. 2.05; p = 0.7). FCGM-detected hypoglycemia rates were comparable (5.5 vs. 5.4 events/week; p = 0.65), but hypoglycemia was significantly more frequent in the morning/noon than pre-sunset (1.9 vs. 0.43 events; p < 0.001). The ambulatory glucose profiles of the early versus late regimens were glucose management indicator: 7.58 ± 1.01 versus 7.49 ± 0.9 (p = 0.36), time in range (70–180 mg/dL) of 46.9 ± 17.3% versus 47.9 ± 17.3% (p = 0.99), time below range (<70 mg/dL) of 8.6 ± 14.3% versus 7.8 ± 7.6% (p = 0.15), time above range (>180 mg/dL) of 45.8 ± 22.03% versus 44.5 ± 20.1% (p = 0.6), and glucose variability of 39.3 ± 10.5% versus 40.6 ± 6.5% (p = 0.005).Adjusting Suhoor timing was well tolerated and offered flexibility. Further research is needed to optimize fasting strategies for individuals with T1D.
Keywords: Ramadan; fasting; early Suhoor; late Suhoor; type 1 diabetes